DIFFERENT PRODUCTS WEAVING HANDICRAFTS - Selvi K asman; Novesar Jamarun; Hamzah Hamzah (LP2MP3M, INSTITUT SENI INDONESIA SURAKARTA, 2019)
Increasing woven products utilizing woven as a base material for various handicraft products, Diversification emphasizes towards application through coaching and training given to artisans, so that this program can improve skills, increase knowledge and insight of craftsmen on products they can produce using woven material. In addition to the application of new weaving design motifs, training is conducted to diversify handicraft products using woven materials and modify woven fabrics with other materials such as woven bamboo, rattan, and pandanus, as well as other materials to produce more varied weaving craft products. (2) Woven handicraft modified weaving, (3) Souvenirs, (4) Pillow cushions, (5) Mattress pads, (6) Hoods Lamp. Diversification of products while maintaining quality, and maintaining the characteristics of woven unggan. Development and training provided is an effort to improve the quality of weaving through diversification of handicraft products, to create new entrepreneurs who are able to compete in the global market. Diversification of handicraft products that have high creativity value will be able to increase the selling value of the product. So as to strengthen the Indonesian woven products as a whole. Tenun Unggan as an element of potential local culture as a local genius because it has proven its ability to survive so as to enrich the national culture.